Tuning the plasmonic resonance in TiN refractory metal - Anchal Rana; Neeraj Kumar Sharma; Sambhunath Bera; Aditya Yadav; Govind Gupta; Abhimanyu Singh Rana (Scientific Reports, 2024)
Abstract Plasmonic coatings can absorb electromagnetic radiation from visible to far-infrared spectrum for the better performance of solar panels and energy saving smart windows. For these applications, it is important for these coatings to be as thin as possible and grown at lower temperatures on arbitrary substrates like glass, silicon, or flexible polymers. Here, we tune and investigate the plasmonic resonance of titanium nitride thin films in lower thicknesses regime varying from ~ 20 to 60 nm. High-quality crystalline thin films of route-mean-square roughness less than ~ 0.5 nm were grown on a glass substrate at temperature of ~ 200 °C with bias voltage of − 60 V using cathodic vacuum arc deposition. A local surface-enhanced-plasmonic-resonance was observed between 400 and 500 nm, which further shows a blueshift in plasmonic frequency in thicker films due to the increase in the carrier mobility. These results were combined with finite-difference-time-domain numerical analysis to understand the role of thicknesses and stoichiometry on the broadening of electromagnetic absorption.